Developing an online community for UiTM UFM using web 2.0 standards / Mohd. Yunos Mazlan - Mazlan, Mohd. Yunos (2007)
The rapid growth of the Internet has provide many opportunities for students to improve their learning medium and environment. One of the way is to participate in online communities on the Internet, and share experience or knowledge among the members of the community. This can give them a glimpse of what is happening in the real world and make friends. Internet technology is evolving rapidly by days be it software or hardware. Technology launched today, may become obsolete in merely two months. The technology transition of Web 1.0 to Web 2.0 brings a lot more changes and advancement. Web 2.0 offers users rich experience, more stability and faster response. By combining both online community and Web 2.0 element, the research is about developing an online community for UFM using Web 2.0 standards. The research also includes recommendation on how the UFM online community can be an added value to UiTM.